2015
DOI: 10.1049/iet-pel.2014.0591
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency comparison between Si and SiC‐based implementations in a high gain DC–DC boost converter

Abstract: An efficiency comparison between a boost converter implemented with silicon (Si) devices and the same converter implemented in the other three cases, that is, employing two combinations of silicon carbide (SiC) devices and a mixture of Si and SiC elements is presented. The converter has been designed for high-voltage low-power applications required by light-emitting diode (LED) lighting. The comparison is performed on an equal basis and discusses the influence on the converter efficiency of the semiconductor p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…4 it can found that the maximum load current at BM occurs at D ST = 0.1163. For the design parameters and by substituting D ST = 0.1163 in (32), a minimum magnetising inductance as a function of maximal load current at BM (I oB max ) can be obtained.…”
Section: Input Current Ripple and Minimum Inductance For Ccmmentioning
confidence: 99%
See 1 more Smart Citation
“…4 it can found that the maximum load current at BM occurs at D ST = 0.1163. For the design parameters and by substituting D ST = 0.1163 in (32), a minimum magnetising inductance as a function of maximal load current at BM (I oB max ) can be obtained.…”
Section: Input Current Ripple and Minimum Inductance For Ccmmentioning
confidence: 99%
“…Nevertheless, low efficiency at high voltage gain is a concern for any dc-dc converter. Some investigations have shown that the use of Silicon Carbide semi-conductors has a considerable efficiency improvement in high gain converters [32]. Measured efficiency of the proposed CIC converter for various input voltage is drawn in Fig.…”
Section: Input Current Ripple and Minimum Inductance For Ccmmentioning
confidence: 99%
“…One of the key concerns for end users of IGBT power modules is the power loss characteristics of the devices. Since the traditional silicon (Si) based devices have almost reached their upper limit of power loss optimisation, the wide bandgap (WBG) materials [4][5][6], such as silicon carbide (SiC) and gallium nitride, have been identified as promising alternatives due to their superior material properties, such as higher breakdown voltage level, higher barrier heights, higher operation temperature and higher thermal conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…A high voltage gain boost converter was designed for low power application (≈ 20 W) which is suitable for light emitting diode (LED). DC-DC converter efficiency was improved from 76 to 89% and 68 to 81% with variation in the switching frequency from the 120 kHz to 20 kHz at 600 V and 900 V output voltage, respectively [12]. Han et al have performed the comparative study on the efficiency, weight and volume of SiC and Si based bidirectional DC-DC converter for the hybrid electrical vehicle.…”
Section: Introductionmentioning
confidence: 99%